Desempenho de bovinos em pastejo submetidos a duas frequências de suplementação no período da seca - Canesin, Roberta Carrilho [UNESP]; Berchielli, Telma Teresinha [UNESP]; Reis, Ricardo Andrade [UNESP]; Rey, Fernando Sebastián Baldi [UNESP]; Resende, Kleber Tomás de [UNESP]; De Almeida Teixeira, Izabelle Auxiliadora Molina [UNESP] (Universidade Estadual de Maringa, 2009)
This work was carried out to evaluate different frequencies of supplementation during the dry season. Forty-eight Nellore steers with 320 kg of initial live weight were fed with Brachiaria brizantha cv. Marandu pasture on a continuous stocking rate. The animals were submitted to following treatments: Daily supplementation and supplementation three times a week. The animals in both treatments received 7 kg of supplementation animal -1 weekly, and were weighted at 28-day intervals. The data were analyzed by the MIXED procedure in SAS (2004), with measurements repeated over time. The study observed average forage allowance of 4.2 tons of DM ha-1, with 3.5% CP, 82.24% NDF and 64.97% ADF. There was no difference (p < 0.01) among daily weight gains of animals who received daily supplementation and those received supplementation three times a week (0.23 and 0.13 kg day -1, respectively). Therefore, the supplementation intervals did not influence steer performance during the dry season.
Steers performances in grazing submitted by two supplementation intervals during dry season
Keywords: Marandu; Rotational grazing fixed; Supplement; Weight gain; Animalia; Brachiaria; Urochloa brizantha